The effect of jacobson's progressive relaxation technique on postoperative pain, activity tolerance, and sleeping quality in patients undergoing gynecological surgery - Heba Abdel-Fatah Ibrahim; Wafaa Taha Elgzar; Reda Mhmoud Hablas (Wolters Kluwer Medknow Publications, 2021)
Background: Inadequate pain management and sleep disturbances of patients undergoing gynecological surgery are associated with delayed recovery time. This study aimed to assess the effect of Jacobson's Progressive Relaxation Technique (JPRT) on postoperative pain, activity tolerance, and sleeping quality in patients undergoing gynecological surgery. Materials and Methods: A randomized controlled clinical trial conducted at Obstetrics and Gynecology Department/Damanhour educational institute, Elbehira, Egypt. The study sample involved 116 patients undergoing gynecological surgery who were equally distributed between intervention and control groups. Data collected from April to September 2019. Four tools were used for data collection: Demographic data interview schedule, pain analog scale, activity tolerance questionnaire, and the Groningen sleeping quality scale. For the intervention group, the women were asked to perform JPRT for 30 min on the second and third postoperative day, three times a day. SPSS 23.0 is used to analyze data using Chi-square, Fisher's exact, independent t-test, and Analysis of Covariance (ANCOVA). A significance level considered at p < 0.05. Results: The study results showed that JPRT significantly improves pain, sleep quality, and activity tolerance mean scores among the intervention group compared to the control group (F1 = 119.13, p < 0.001), (F1 = 361.49, p < 0.001), and (F1 = 157.49, p < 0.001), respectively. ANCOVA results showed that 33% of the decreased pain score, 12% of decreased sleeping quality score, and 26% of improved activity tolerance score are due to JPRT. Conclusion: JPRT should be offered as a part of standard postoperative nursing care for patients undergoing gynecological surgery to control pain and improve sleeping quality and activity tolerance.